FINANCIAL PERFORMANCE AND GOING CONCERN OPINION - Putri, Eldiana Yanuar Anisa; Suryani, Ani Wilujeng (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
The decline in business activities due to the COVID-19 pandemic worsened the company's financial condition and allowed the company to obtain a going concern opinion (GCO). The company obtains GCO when there is a risk that threatens business continuity. Management needs to maintain the company's financial condition in order to maintain the company's business continuity. This study aims to determine the effect of banking financial conditions using CAMEL analysis on GCO from 2019 to 2021. The CAMEL analysis used consists of capital adequacy, asset quality, management efficiency, profit, and liquidity. Logistic regression analysis is used to test the hypothesis and shows that inefficient management has a positive effect on GCO, while capital adequacy, asset quality, profit, and liquidity have no effect. Therefore, the company needs to maintain management efficiency by managing costs incurred from the income received properly so as to minimize GCO acquisition.